IMPLEMENTATION OF BILLING POS (POINT OF SALE) APPLICATION BASED ON ANDROID ON BOSS PLAYSTATION - Surya Efriya, Almi; Martin, Afrizal; Irviani, Rita (JMBI (Journal of Marketing and Business Intelligence), 2023)
BOSS Playstation is a Playstation game rental place in Pringsewu, BOSS Playstation has a transaction activity that involves customers and working employees, it is not uncommon for each party involved to have misunderstandings regarding transactions, both duration and rental fees. For this reason, the authors see the need for an application design that can handle these problems, in this case a billing application that can later manage schedules or activities related to leasing carried out by customers. With an Android-based application, it is hoped that later the application can be used freely by the operator on duty, the application can also function as a place for recording revenue and time earned on that day by the operator on duty. There are two applications that will be the result of this design, namely an application to monitor billing time and an application to manage all transactions needed in this business such as rental prices, duration, package names, to available food, as well as to monitor revenue earned by BOSS Playstation.